Inflammation mediates the association between muscle mass and accelerated phenotypic aging: results from the NHANES 2011–2018 - Bao, Shifu; Jimu, Weibu; Mu, Nai; Yan, Fang; Xing, Shuxing; Li, Tao; Zhou, Zheng (Frontiers in Nutrition, 2025)
BackgroundMuscle mass plays a pivotal role in health maintenance, yet its connection to biological aging remains underexplored. This study investigates the association between appendicular skeletal muscle mass index (ASMI) and phenotypic age(PhenoAge), while examining the mediating role of systemic inflammation.MethodsThe analysis included 7,440 participants from the NHANES 2011–2018. Phenotypic Age Acceleration (PhenoAgeAccel) was calculated as the residuals from regressing PhenoAge on chronological age. Multivariable linear regression analyses were performed to assess the association between ASMI and PhenoAgeAccel. Mediation analysis was conducted to quantify the extent to which systemic inflammation contributes to this association.ResultsOur analysis revealed that higher ASMI is linked to slower biological aging, as evidenced by lower PhenoAgeAccel (β = −0.48, 95% CI: −0.66 to −0.29, p = 0.0001). Systemic inflammation partially mediated this effect, with a mediation proportion of 35.1%. The association varied notably across demographic and health-related subgroups, being particularly significant in females, individuals with obesity, and those with lower physical activity.ConclusionThese findings highlight the critical importance of muscle mass in slowing biological aging, with systemic inflammation emerging as a key biological mediator. The public health implications are substantial, suggesting that targeted interventions—such as resistance training, anti-inflammatory diets, and personalized medical approaches—could play a pivotal role in decelerating biological aging and improving long-term health outcomes.